Surviving solitary: living and working in restricted housing units - Rudes, Danielle S. (Stanford University Press, 2022)
Living and working in the RHU -- Risk -- Relationships -- Rules -- Reentry -- Reform -- Reversal and revision -- Epilogue : behind the walls.